Whole-brain monosynaptic inputs and outputs of leptin receptor b neurons of the nucleus tractus solitarii in mice - Lu Sun; Mengchu Zhu; Meng Wang; Yinchao Hao; Yaxin Hao; Xinyi Jing; Hongxiao Yu; Yishuo Shi; Xiang Zhang; Sheng Wang; Fang Yuan; Xiang Shan Yuan (Brain Research Bulletin, 2023)
The nucleus tractus solitarii (NTS) is the primary central station that integrates visceral afferent information and regulates respiratory, gastrointestinal, cardiovascular, and other physiological functions. Leptin receptor b (LepRb)-expressing neurons of the NTS (NTSLepRb neurons) are implicated in central respiration regulation, respiratory facilitation, and respiratory drive enhancement. Furthermore, LepRb dysfunction is involved in obesity, insulin resistance, and sleep-disordered breathing. However, the monosynaptic inputs and outputs of NTSLepRb neurons in whole-brain mapping remain to be elucidated. Therefore, the exploration of its whole-brain connection system may provide strong support for comprehensively understanding the physiological and pathological functions of NTSLepRb neurons. In the present study, we used a cell type-specific, modified rabies virus and adeno-associated virus with the Cre-loxp system to map monosynaptic inputs and outputs of NTSLepRb neurons in LepRb-Cre mice. The results showed that NTSLepRb neurons received inputs from 48 nuclei in the whole brain from five brain regions, including especially the medulla. We found that NTSLepRb neurons received inputs from nuclei associated with respiration, such as the pre-Bötzinger complex, ambiguus nucleus, and parabrachial nucleus. Interestingly, some brain areas related to cardiovascular regulation—i.e., the ventrolateral periaqueductal gray and locus coeruleus—also sent a small number of inputs to NTSLepRb neurons. In addition, anterograde tracing results demonstrated that NTSLepRb neurons sent efferent projections to 15 nuclei, including the dorsomedial hypothalamic nucleus and arcuate hypothalamic nucleus, which are involved in regulation of energy metabolism and feeding behaviors. Quantitative statistical analysis revealed that the inputs of the whole brain to NTSLepRb neurons were significantly greater than the outputs. Our study comprehensively revealed neuronal connections of NTSLepRb neurons in the whole brain and provided a neuroanatomical basis for further research on physiological and pathological functions of NTSLepRb neurons.